BARISAN AUSLANDER-REITEN - MARIS, IKA METIZA (Sainstek : Jurnal Sains dan Teknologi, 2010)
This paper introduces Auslander-Reiten Sequences in mod A, where A is a finite dimensional -algebra. We will also introduces almost split morphism, as a special form of morphisms, which will provide a natural way to present the form of Auslander-Reiten sequences. These sequences are particulary useful in representation theory of algebras.Key words: almost split morphisms, , irreducible morphisms, almost split sequences